RWANDA'S PARTNERSHIP WITH THE FAO: ADVANCING AGRICULTURAL SUSTAINABILITY AND MEETING THE SDGS - Izza, Atina; Anisa, Farah (Journal of Social Political Sciences, 2024)
Rwanda's efforts to rebuild the country after the 1994 genocide received a good response from the international community. Thanks to the agricultural industry, Rwanda's economy is growing rapidly. The agricultural sector is a major contributor to Rwanda's economic growth, employing around 70% of its population and contributing 30% of the country's GDP. Even compared to other African countries, Rwanda experienced the fastest economic growth, despite traumatic post-genocide rehabilitation. The importance of the agricultural sector to Rwanda's economy makes it necessary to establish partnerships with international organizations such as FAO. Cooperation between FAO and Rwanda is then included in the Country Programming Framework: 2019 -2023. Not only to create sustainable agriculture, FAO and Rwanda's collaboration is also aimed at achieving Sustainable Development Goals (SDGs). Thus, this research will discuss in more depth how cooperation between Rwanda and FAO can contribute to achieving agricultural sustainability and the Sustainable Development Goals. The aim is to better understand how international organizations have a role in the development of developing countries. To answer this, this research will use secondary data analysis methods, both qualitative and quantitative. And the results found were that empowerment programs initiated by FAO had an important role in helping develop Rwanda's agricultural sector and had an impact on achieving several SDGs goals in Rwanda. However, it cannot be denied that the problems in Rwanda's agriculture have not been completely resolved. Challenges such as climate change are one that is still a problem for many countries, including Rwanda.